2021
DOI: 10.1111/add.15654
|View full text |Cite
|
Sign up to set email alerts
|

Association between dynamic dose increases of buprenorphine for treatment of opioid use disorder and risk of relapse

Abstract: Background and Aims: Dynamic, adaptive pharmacologic treatment for opioid use disorder (OUD) has been previously recommended over static dosing to prevent relapse, and is aligned with personalized medicine. However, there has been no quantitative evidence demonstrating its advantage. Our objective was to estimate the extent to which a hypothetical intervention that increased buprenorphine dose in response to opioid use would affect risk of relapse over 24 weeks of follow-up.Design: A secondary analysis of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 51 publications
2
3
0
Order By: Relevance
“…The conclusions that may be drawn from our re-analysis using the stochastic interventional direct and indirect effects complement those previously reported in the investigations of Lee et al (2018), who evaluated the total effect of BUP-NX (versus XR-NTX) treatment on OUD relapse, and Rudolph et al (2020a), who used the interventional mediation analysis approach of (limited to static interventions on A) to examine differences in relapse risk between homeless and non-homeless participants. Importantly, our substantive conclusion -that dose increases directly lower the risk of relapse -agree generally with those of Rudolph et al (2020b), who found that dose increases directly lowered risk of OUD relapse when such dose increases followed opioid use. Notably, our proposed (in)direct effects and estimation approach differ from previous efforts in three important ways: (i) our causal effect definitions remain unaltered in the presence intermediate confounders affected by exposure and may be re-evaluated in randomized trials, (ii) the flexible estimators we introduce eschew restrictive modeling assumptions by incorporating state-of-the-art machine learning in the estimation of nuisance parameters, and (iii) our strategy provides an analog to a dose-response analysis by allowing for the risk of OUD relapse to be traced out across changes in the odds of exposure to a schedule in which BUP-NX dose is increased repeatedly early in treatment.…”
Section: Efficient Targeted Minimum Loss Estimatorsupporting
confidence: 89%
“…The conclusions that may be drawn from our re-analysis using the stochastic interventional direct and indirect effects complement those previously reported in the investigations of Lee et al (2018), who evaluated the total effect of BUP-NX (versus XR-NTX) treatment on OUD relapse, and Rudolph et al (2020a), who used the interventional mediation analysis approach of (limited to static interventions on A) to examine differences in relapse risk between homeless and non-homeless participants. Importantly, our substantive conclusion -that dose increases directly lower the risk of relapse -agree generally with those of Rudolph et al (2020b), who found that dose increases directly lowered risk of OUD relapse when such dose increases followed opioid use. Notably, our proposed (in)direct effects and estimation approach differ from previous efforts in three important ways: (i) our causal effect definitions remain unaltered in the presence intermediate confounders affected by exposure and may be re-evaluated in randomized trials, (ii) the flexible estimators we introduce eschew restrictive modeling assumptions by incorporating state-of-the-art machine learning in the estimation of nuisance parameters, and (iii) our strategy provides an analog to a dose-response analysis by allowing for the risk of OUD relapse to be traced out across changes in the odds of exposure to a schedule in which BUP-NX dose is increased repeatedly early in treatment.…”
Section: Efficient Targeted Minimum Loss Estimatorsupporting
confidence: 89%
“…Higher TMbup doses have been associated with improved treatment retention and decreased relapse risk in some observational studies 11,15 . In addition to these reported associations, our findings suggest an association between higher first 30-day TMbup doses and decreased subsequent mortality.…”
Section: Discussionsupporting
confidence: 77%
“…11,13 Clinical guidelines vary on TMbup's target dose and how quickly it should be reached, but it is agreed that most patients reach stable maintenance daily doses between 4 mg and 24 mg, with 16 mg being a common target. 7,14 Despite prior findings suggesting that higher doses of buprenorphine (eg, >16 mg daily) may provide better treatment outcomes, such as decreased discontinuation and return to opioid use, 10,11,15 limited information is available about the associations between TMbup doses and subsequent risk of death.…”
mentioning
confidence: 99%
“…High-dose bup/nal is an adaptive dosing protocol; the patient receives an additional bup/nal dose only if the Clinical Opiate Withdrawal Scale (COWS) score is 13 or above. Evidence suggests that higher doses and adaptive dosing are associated with reduced opioid use and increased treatment retention 8 …”
mentioning
confidence: 99%
“…Evidence suggests that higher doses and adaptive dosing are associated with reduced opioid use and increased treatment retention. 8 Buprenorphine extended-release subcutaneous injection (buprenorphine ER) also has the potential to increase treatment retention rates. Buprenorphine ER produces a higher and more constant serum buprenorphine level than buprenorphine SL, and its duration of action is between 28 and 42 days, eliminating the need for daily medication use.…”
mentioning
confidence: 99%